Transient Hiccups Associated with Oral Dexamethasone - Mark E. Peacock (Case Reports in Dentistry)
Hiccups, or singulata (hiccup is singultus), are commonly experienced by most people at one time or another and are usually brief and self-limiting. Although pharmacotherapeutic agents are not generally considered causal in the etiology of hiccups, many clinicians empirically associate episodic hiccups in their patients as being drug induced. The two classes of drugs most often cited as causing hiccups are corticosteroids and benzodiazepines. This report involved a patient who was given preoperative dexamethasone and developed hiccups before anesthesia and surgery commenced. He at no time was in distress, and the surgical procedure was completed without complication. By the second postsurgical day his hiccups were resolved completely. Although the association may be anecdotal, many clinicians consider hiccups a potential side effect of steroid therapy, especially high doses of steroids. Of interest in this case is the relatively low dose of corticosteroid used, albeit apparently linked to his hiccups. Practitioners should be aware of this potential condition.